Groundwater as a potential cause of Chronic Kidney Disease of unknown etiology (CKDu) in Sri Lanka: a review - Sachithra Imbulana; Kumiko Oguma (IWA Publishing, 2021)
The cause of Chronic Kidney Disease of unknown etiology (CKDu) in the rural dry zone of Sri Lanka remains unidentified, despite vast research efforts that brought about an extensive list of potential risk factors. Among these, the long-term exposure to various nephrotoxic elements through drinking groundwater was widely suspected owing to the unique geographical distribution of the disease. This review focuses on such well-known hypotheses suspecting the relations with fluoride, hardness, major ions, heavy metals, metalloids, organic matter, agrochemical residues, pathogens, and bacterial toxins in the groundwaters of the CKDu-endemic region. It was comprehensively discussed why each of these constituents was considered a risk factor of CKDu, how could they possibly trigger the pathogenesis of the disease, what was the evidence that supported or failed each hypothesis, and whether providing safe drinking water had been effective at mitigating the progression of the disease. Although plenty of circumstantial evidence supported an etiology related to groundwater for CKDu, it was impossible to elucidate the cause-effect relationships between drinking impaired groundwater and the occurrence of the disease. Future research should be effectively designed to clarify the role of groundwater in the onset of CKDu by taking into account the gaps in past research. HIGHLIGHTS Most updated review on the underlying topic to cover all relevant original studies up to 2020.; An intensive discussion focusing on groundwater as a potential cause of CKDu.; Useful for identifying the gaps in previous research and seeking new methods to elucidate the cause of CKDu.; Highly relatable to those who are interested in exploring health implications of drinking water.;